Antisense strategies for the treatment of hematological malignancies and solid tumors - Kronenwett, Ralf; Haas, Rainer (Annals of hematology, 1998)
If malignant growth is considered the result of abnormal gene expression, it is reasonable to use antisense nucleic acids for the treatment of malignant diseases. Antisense oligonucleotides can specifically down-regulate gene expression, and a number of first-generation antisense compounds have entered human clinical trials. In this review, some aspects relevant for the development of antisense-based drugs, such as the selection of appropriate target sequences, cellular delivery, and design of a clinical study, are described, using bcr-abl-oncogene-directed antisense oligonucleotides as an example. In addition, potential target genes for antisense inhibition in hematology and oncology, including oncogenes and adhesion molecules, are summarized. Down-regulation of such adhesion molecules as members of the immunoglobulin superfamily and integrins may provide new modalities for mobilization of CD34+ hematopoietic stem cells into the peripheral blood. The review closes with an overview of ongoing clinical trials in the treatment of malignant diseases by antisense oligonucleotides.